Blind Man's Bluff - cruel revelations through the study of architectural artefacts - Berlein, Darren (School of Architecture, Planning and Geomatics, 2020)
This dissertation is an attempt to understand the Bluff Headland of Durban by uncovering its hidden systems and ideas. By studying the abandoned built fabric visible on site including a whaling station, the ideas that once embedded themselves within those structures reveal much larger societal notions and hidden systems. The Bluff is of a particular interest in its relation to modernity as it is framed as a blind spot hidden in the development of Durban. Many of the artefacts found on site today are abandoned and owe themselves to particular epochs that have faded such as the abandoned World War 1 bunkers and the abandoned whaling station. However, Durban Central Sewage Treatment Works nestles itself in between these abandoned structures away from any engagement with the city anonymously pumping sewage into the ocean. This dissertation explores the horrors that once nested themselves in these structures through multiple modes of making, in particular the use of the camera and the body, as method of engaging with site artefacts cross-referenced with archival-research. The design project attaches itself to the ruined whaling station and manifests itself as a space of remembrance for the past systems that have once occurred. It also looks to the future of human impact on its environment by initially opening a counter memorial that allows the building to later mature into a museum through the passage of time. The natural action of the waves wash away the sand formwork that is used to cast the museum. Additionally visitors to the counter memorial are also invited to flense and wash some of the sand away to understand timescales of the natural world. These erosive processes will then allow the space to open to its full capacity, in time, taking direct influence from the process of whaling.